The DNA Sensor IFIX Drives Proteome Alterations To Mobilize Nuclear and Cytoplasmic Antiviral Responses, with Its Acetylation Acting as a Localization Toggle - Timothy R. Howard (American Society for Microbiology, 2021)
Mammalian cells must be able to detect and respond to invading pathogens to prevent the spread of infection. DNA sensors, such as IFIX, are proteins that bind to pathogen-derived double-stranded DNA and induce antiviral cytokine expression.